Self-organized Learning and its Relationship to Positive Thinking and Problem-solving among Taif University Students - Al-Otaibi, Ghadeer Abdullah Ayed (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to identify the level of self-regulated learning, positive thinking, and problem solving among Taif University students, and to reveal the relationship between self-regulated learning and positive thinking among Taif University students, as well as revealing the relationship between self-regulated learning and problem solving among Taif University students. The study used the descriptive correlational method, and the sample consisted of (108) male and female students randomly selected from students at Taif University. The tools used included the self-regulated learning scale prepared by Farhan (2020), the positive thinking scale prepared by Al-Quraishi (2012), and the solution scale. The problems were prepared by Hebner and Patterson, and translated by Jarwan (1986). The study reached the following results: There is a statistically significant correlation between self-regulated learning and positive thinking among a sample of male and female students at Taif University. There is a statistically significant correlation between self-regulated learning and problem solving among a sample of male and female students at Taif University. Based on the results, the researcher recommended paying attention to establishing guidance programs to encourage students to engage in self-regulated learning, as well as holding training courses to train faculty members on using self-regulated learning and developing its skills among students.